A novel cellulosic non‐enzymatic nanosensor based on carbon shell silver (Ag@C) nanoparticles for colorimetric detection of Chlorpyrifos in agricultural products. Issue 10 (6th October 2022) - Bilal, Sehrish; Saleem, Shaifa; Akhtar, Naeem; Sami, Amtul Jamil; Gokce, Gultekin; Hayat, Akhtar
Abstract: Background: The precise detection and quantification of organophosphorus pesticides are highly required to ensure food safety. The non‐enzymatic nanosensor technology has appeared as an efficient method to replace conventional analytical techniques of pesticide detection. The utilization of carbon‐based nanomaterials and metal nanoparticles has shown great potential to develop non‐enzymatic nanosensors for the sensitive and selective sensing of food contaminants. Results: In this study, bifunctional carbon shell silver nanoparticles (Ag@C NPs) having oxidase‐like properties and advanced optical activities were used as nanozymes for visual detection of highly toxic organophosphorus pesticide (OP), Chlorpyrifos. The as‐prepared nanomaterial was characterized for its structural and morphological features. The nanosensor was fabricated by immobilizing Ag@C NPs in the network of sodium alginate gel over a cellulosic paper disc. The detection was based on the inhibition of oxidase‐like activity of Ag@C NPs by the adsorption of pesticide which blocks the accessibility of substrate to produce the blue‐colored product. Under the optimized conditions, the fabricated sensor showed potential analytical response for Chlorpyrifos providing a dynamic linear range from 0–350 ng/mL with a limit of detection, of 0.097 ng/mL and limit of quantification, of 0.293 ng/mL. In addition, the devised sensor was able to recover Chlorpyrifos from spiked wheat, apple, and water samples with excellent recovery percentages. Further, the constructed nanosensor exhibited excellent selectivity and specificity to Chlorpyrifos. Conclusion: The fabricated surface provides a rapid, selective, low cost and portable detection method for the real‐time detection of OP traces from food and environmental samples.